Popular and Solidary Financial System and its evolution since the implementation of the new Organic Law of Popular and Solidarity Economy in Ecuador - Ortega Pereira, Jaime Roder; Borja Borja, Fernando Marcelo; Aguilar Rodríguez, Iliana Elizabeth; Moreno Cazar, Willam Marcelo (Cooperativismo & Desarrollo, 2017)
Introduction: the present article analyzes the evolution of the main data of the credit and savings cooperatives (cscs) that were under the control of the National Cooperatives Directorate (ncd) and the Ministry of Economic and Social Inclusion (mesi), as well as the main data of the cooperatives that belonged to the Superintendency of Banks (sb) and which later became part of the Popular and Solidary Financial System (psfs) in the first years of the Organic Law of Popular and Solidarity Economy (olpse). All of these are under the control of the Superintendency of Popular and Solidarity Economy (spse).Methodology: A financial analysis of variations and trends was applied to determine the psfs growth after the application of the olpse.Results: Credit and savings cooperatives have consolidated their participation in the market, passing from representing 17.65 % to 20.20 % of the entire national financial system in the analyzed period.Conclusions: Despite the systemic adverse effect, the cooperatives had an average compound annual growth of 8.98 %, a figure substantially higher than the growth of the entire National Financial System (nfs) of 1.86 %, and of the banks in a 0.20 % in this same period.
Keywords: banks; credit and savings cooperatives; popular economy; solidarity economy; financial system